Environmental performance and financial performance : an empirical study on manufacturing companies in Jeddah, Saudi Arabia - Hamoudah, Manal Mohammed (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
This thesis uses Resource-Based Vic11 (RBV) framework to examine whether imprmed environmental perfonnance (EPl leads to better financial performance (FP) in manufacturing compames in Saudi Arabia. To ensure an appropriate match of measures used to evaluate EP and FP within the RBV framework. the thesis measures EP and rP in both their strategic and operational dimensions. EP is measured through the strategic indicators of top management commitment (TMC) and EMS-ISO 1400 I and the operational indicators of programmes to reduce em ironmental impact (PRE!) and emironmental strategy (ES). ror rP. the strategic indicator is shareholder value and the operational indicators are profitability and liquidity. A revie11 of the existing literature reveals the lack of a theoretical foundation and methodological shortcomings in measuring EP and analyzing the relationship between EP and rP. leading to inconsistent results. The thesis addresses these issues. A questionnaire sun cys the subjecti1 e perceptions of managers in evaluating their companies· EP and FP. followed up by semi-structured in ten iews conducted with ten of the sun ey respondents. The data obtained was analysed using a structural model based on Partial Least Square (PLS) analysis. Two main models were presented in this study to test the hypotheses. The tirst model is the second-order structural model to examine the positive effect of EP on FP. The second model is the tirst-order structural model to explore the positive effect of each EP indicator on FP. In addnion. the present study imcstigates the moderating e!Tect of company size and industry classification. The tinding generated !rom the tirst model pro1 ides solid support of the mam hypothesis of EP and contim1s the RB\' framework. The findings of this model also show that the most sigmticant mdicator related to the underlying EP construct is the T\1C indicator. Based on the tindings obtained from the second modeL only the T\1C indicator has significant posni1·e Impact on FP. The results produced tr01n both models continn the signi ticance of strategic dimension of EP. especially the proactive im oil ement of top management in em ironmental protection. The result of the moderating e!Tect 11 as neutral. The findings !rom the interviews prmidc support for the main hypothesis and suggest some explanation of the unexpected sun ey results. Essentially. the results of this study arc rele1ant in light of the many roles that can be played by policy makers which might pro1 e to be beneficial for imprm ing the EP of companies in the Saudi Arabian context.